Book review: Han, B. C. (2025). Speaking About God: A Dialogue with Simone Weil. Paidós. (Palimpsesto, 2026)
Byung-Chul Han tackles Simone Weil’s thought with a double dose of audacity to discuss God in the current context. The review highlights how mainstream philosophy has marginalised the spiritual dimension and how the growing digital takeover is overwhelming our attention, flattening it and preventing human beings from opening themselves up to deep listening.Han revisits the major Weilian concepts: attention as a concavity opposed to idolatry; beauty and misery as paths to the supernatural; the contrast between gravity and grace; and decreation as a rooting in absence. Attention is the essence of prayer, and its current crisis—accelerated by digitalisation and the total availability of reality—forms part of the structural causes of the absence of God.In the face of neoliberal spirituality, which instrumentalises the soul for the sake of performance, we find in Weil a reference to a purifying atheism that recognises in every form of love an implicit love of God.  Furthermore, and unlike both servile and artificial intelligence, she urges us towards a careful reading of reality, the only means capable of generating something truly new.
Keywords: Attention; grace; gravity; reading; decreation